Ulnar Shortening Osteotomy for Ulnar Impaction Syndrome - Doherty, Christopher; Gan, Bing Siang; Grewal, Ruby (Journal of Wrist Surgery, 2014)
Background Ulnar impaction syndrome is a condition in which the ulna impacts on the ulnar carpus. This most commonly occurs when the ulna is longer than the radius, but it can also occur in wrists with ulnar neutral and ulnar negative variance.Materials and Methods In this paper we outline our surgical technique for ulnar shortening osteotomy. A previously published retrospective case series of 28 patients treated at our center is presented. Fifty consecutive patients who underwent ulnar shortening osteotomy (USO) for ulnar impaction syndrome were approached for study, and 28 consented to review. Mean preoperative ulnar variance was +2.3 mm, and mean postoperative ulnar variance was –0.8 mm. Mean follow-up time was 21.2 months (8 to 41 months) and ten of 28 were receiving workers' compensation. Mean preoperative pain score (visual analog scale; VAS) was 7.9. Univariate analysis was performed to assess clinical and demographic data. In addition, subgroup analysis of workers' compensation patients and smokers was performed.Description of Technique A longitudinal incision over the subcutaneous border of the ulna is used to expose the ulna between the distal and middle third of the ulna from the ulna styloid. Preoperative posteroanterior (PA) X-rays are reviewed to determine the amount of shortening required, with a goal of creating –2 mm variance postoperatively. A 6-hole dynamic compression plate is predrilled distally prior to performing two oblique osteotomies separated by the desired shortening length. The fragments are reduced, controlling for rotation, and plated using compression. In some cases, a lag screw is employed across the oblique osteotomy site.Results Mean pain scores were significantly reduced postoperatively (VAS 7.9 versus 3.1, P < 0.0001). The mean Disabilities of the Arm, Shoulder, and Hand (DASH) score was 37.2 postoperatively. Flexion, extension, and supination were reduced compared with the contralateral unaffected extremity (84.6%, 85.3%, and 86.9% of normal). Patients receiving workers' compensation and smokers had significantly more pain postoperatively (VAS 5.2 vs. 2.0, P = 0.0002 and VAS 4.4 vs 2.4, P < 0.05, respectively). Eleven of 28 patients required hardware removal for plate irritation, and five of 28 patients had a nonunion.Conclusion We present our surgical technique for ulnar shortening osteotomy. Pain was significantly improved in our population; however, patients receiving workers' compensation and smokers had less improvement in pain and higher disability scores.
Keywords: ulnar shortening osteotomy; ulnar impaction syndrome